FREQUENCY OF RIGHT VENTRICULAR INFARCTION AND IN-HOSPITAL OUTCOME AFTER PRIMARY PERCUTANEOUS CORONARY INTERVENTION (PPCI) IN ACUTE INFERIOR MYOCARDIAL INFARCTION (MI) - Mohsin Saif; Shoaib Iqbal Safi; Ariz Samin; Fahd -ur- Rahman; Jasia Bukhari; Sajid Khan (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the frequency of Right Ventricle infarction and in-hospital outcome after primary percutaneous coronary intervention in patients with acute inferior MI.